The Influence of Tiktok Content With Model AISAS on Purchase Intention of Muslim Fashion Products (Case Study: In The Special Region of Jakarta Province) - Sandi Panlevi; Jono Mintarto Munandar; Irfan Syauqi Beik (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The development of social media, especially TikTok, has led to the birth of the social commerce era that changes digital marketing strategies, including for Muslim fashion products. With its short video and live streaming features, TikTok enables quick interaction between creators, sellers, and consumers. Jakarta as an urban center with Muslim majority becomes a strategic market for this industry. In this context, the AISAS (Attention, Interest, Search, Action, Share) model is used to understand the influence of TikTok content on consumer purchase intention, with an emphasis on the importance of relevant, engaging, and emotional content strategies.Purpose: This study analyzes the influence of TikTok content using the AISAS model on Muslim fashion purchase intentions in Jakarta. As a metropolitan area with urban Muslim consumers, Jakarta residents are highly trend-conscious and enjoy shopping.Design/Methodology/Approach: This quantitative research involved 260 male and female TikTok users aged 18-70, Muslim and have watched live streaming and short video marketing in Jakarta using purposive sampling and analyzed using SEM-PLS and descriptive methods.Finding/Result: TikTok's short video marketing proved more effective than live streaming in attracting consumer attention, interest, and search. The AISAS model is a relevant mediator in explaining purchase intention, while product quality, price, and satisfaction play a major role in driving action and share. Authentic and interactive content from short videos and live streaming builds trust, creates trends, and encourages purchase and loyalty to Muslim fashion products.Conclusion: Companies should integrate short videos marketing and live streaming using the AISAS model, emphasizing experience, attention, and engagement. Personal preferences outweigh brand popularity in influencing purchase decisions.Originality/Value: A comparison of TikTok's two content strategies (short video and live streaming) in one study directly linked to purchase intention provides a unique perspective. The comprehensive integration of the AISAS model in the TikTok social media context is an approach that is still rarely used in video-based digital content marketing research. Focus on Muslim fashion products and a specific location (Jakarta), which provides contextual distinctiveness in seeing how global social media trends interact with local culture and preferences. Keywords: AISAS, social media, fashion muslim, purchase intention, TikTok content